(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
The nature of ornamental stones is anisotropic. The heterogeneous characteristics of the anisotropic rocks vary with direction. The highest to lowest strength ratio is known as the anisotropy strength index (ASI). A thorough investigation of the ASI is necessary to determine the best-directed loads for these rocks. On core specimens that have been bored parallel and perpendicular to the weakness planes, this is estimated using both uniaxial compression and point load testing. For this examination, four different rock types had cores that were drilled conventionally and in line with weakness planes. The research shows that drilling cores to weakness planes at a normal or nearly normal angle (90° to 60°) yields the best, most dependable ASI. According to the current study’s findings, the ASI fluctuates depending on how uniformly the mineral content and texture of rocks are. A suggested way to calculate the ASI and the load point strength is also included. This study reveals that the employment of ornamental stone as is (for example, precipitation position is more robust and reliable than that perpendicular form) is critical in determining the resilience of this type of rock and its spatial implementation (e.g. flooring).